INCREASING TRANSPARENCY AND ACCOUNTABILITY ZAKAT, INFAQ AND SADAQAH MANAGER (PSAK 109) - Dea Edryani (RADJA PUBLIKA, 2023)
This article discusses how to understand how the manager of the Zakat Charity Agency (BAZ) interprets accountability in managing zakat, infaq, and shadaqah (ZIS). Accountability in the management of zakat, infaq and shadaqah (ZIS) is needed to build the trust of related parties, such as muzakki, mustahiq, the government and society as a whole. In creating a good zakat governance system, it has the characteristics that there must be transparency and accountability in zakat management, which includes indak and alms management. As a manager of community funds that relies on donors from the community, transparency and accountability in the management of zakat, infaq and shadaqah are the main concerns for the Zakat Charity Agency (BAZ)